Morpho-Semantic Analysis of Some Toponyms with the Prefix “ma” of Oicha Town in the Democratic Republic of the Congo - Mumbere Malonga Mashauri (Current Progress in Arts and Social Studies Research Vol. 3, 2024)
Aims: To analyze the linguistic features of Oicha toponym with the prefix “ma”. In addition, the study aims to awaken the conscience of the younger generation toward discovering the cultural richness found in the Oicha toponyms that can rebuild the roots of their cultural values. Study Design: This study is corpus-driven research based on a qualitative approach; it was carried out in the Department of Education from 2017 to 2023. Methodology: The present study is more inductive and it adopted ethnographic interviews in order to learn about the semantics of the toponyms with the prefix “ma”. It focuses, therefore, on three elements: explicit purpose, ethnographic explanation, and ethnographic questions. The first element of explicit purpose helped in the interview process for sharing the reason behind this research with informants, which is to unveil the linguistic background of some Oicha toponyms that are made up of the prefix “ma” and what “ma” stands for. With the second element of ethnographic explanation, I shared the goal of the study and the third and last element of ethnographic questions helped to examine the reason why the elders decided to name the different villages so and so, moreover, to discover why some toponyms are undergoing some changes. Results: This study discusses the morphological and semantic analysis of Oicha toponyms with the prefix “ma”. The morphological analysis has revealed that the Oicha toponyms with the prefix “ma” are found under the simple form with the structure ma+ substantive theme. The semantics of Oicha toponyms with the prefix “ma” relate to ecology, environment, and tradition. It also brings back the souvenir of people who first lived in the area. The names, in addition, were given to areas in memory of circumstances, experiences, and events that could occur to the inhabitants of that area. Conclusion: From this study, we learn that the Oicha toponyms with the prefix “ma” were not taken by chance, but rather they conveyed a structured message related to ecology and environment in order to pass the message from one generation to another and perpetuate their passage and souvenirs. These toponyms reflect culture, heritage, source of knowledge, and conservation of people’s memories. They represent the Oicha historical background and provide information about natural and cultural conditions.